2020
DOI: 10.1080/17538947.2020.1805037
|View full text |Cite
|
Sign up to set email alerts
|

The role of machine intelligence in photogrammetric 3D modeling – an overview and perspectives

Abstract: The process of modern photogrammetry converts images and/or LiDAR data into usable 2D/3D/4D products. The photogrammetric industry offers engineering-grade hardware and software components for various applications. While some components of the data processing pipeline work already automatically, there is still substantial manual involvement required in order to obtain reliable and high-quality results. The recent development of machine learning techniques has attracted a great attention in its potential to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 126 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…The impacts of SfM – combining high-resolution commercial digital cameras, UASs, automating algorithms and streamlined software – have been profound for aerial photogrammetry. While it still lacks some of the accuracy of high-end systems (Fawcett et al, 2019: 302), SfM has dramatically reduced photogrammetry costs, offers increased user-friendliness, and opens it up to non-expert users (Granshaw, 2018; Qin and Gruen, 2021), thus contributing to the ‘democratization of structural data acquisition’ (Fawcett et al, 2019: 301).…”
Section: The Digitization and Automation Of Photogrammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of SfM – combining high-resolution commercial digital cameras, UASs, automating algorithms and streamlined software – have been profound for aerial photogrammetry. While it still lacks some of the accuracy of high-end systems (Fawcett et al, 2019: 302), SfM has dramatically reduced photogrammetry costs, offers increased user-friendliness, and opens it up to non-expert users (Granshaw, 2018; Qin and Gruen, 2021), thus contributing to the ‘democratization of structural data acquisition’ (Fawcett et al, 2019: 301).…”
Section: The Digitization and Automation Of Photogrammetrymentioning
confidence: 99%
“…In the drive towards full automation of the photogrammetry workflow, machine learning (especially using convolutional neural networks) has the potential to become ‘a game changer’ (Heipke and Rottensteiner, 2020: 10; on the importance of machine learning within geography more broadly, see Lavallin and Downs, 2021). Machine learning is identified as having clear application in several key areas: in image matching and scene triangulation, employing dense imaging mapping (where rather than search an entire image for features this process compares two overlapping images row by row – Kodde, 2016); in interpreting aerial/satellite images – a process known as semantic interpretation; and in georeferencing (adding geographic coordinates to an image) (see Qin and Gruen, 2021).…”
Section: The Digitization and Automation Of Photogrammetrymentioning
confidence: 99%
“…Researchers in the photogrammetry community have proposed methodologies for incorporating semantic information in the photogrammetric pipeline [42][43][44][45]. Research works on improving photogrammetric tasks using semantic information have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In aerial and close-range photogrammetry, automation of the process is extremely important due to the large amount of data to be processed. Machine learning and deep learning are two approaches with many investigations devoted to pipeline automation [5,6]. Concerning deep learning, the relevance of the training dataset on the final robustness of the net represents the major drawback.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning deep learning, the relevance of the training dataset on the final robustness of the net represents the major drawback. Although shared databases and addition of synthetic scenes for the training sets may help to enlarge the generality of these approaches, as highlighted in [7], the computation efforts may rapidly increase, shifting the bottleneck from the lack of automation to the lack of computational resources [8]. In recent years, Convolutional Neural Networks (CNN) have been increasingly used in image analysis and image segmentation, but only nowadays, they started to be used for the improvement of semantic photogrammetry [9], for increasing the level of automation in close-range applications [10], or for background removal with the aim of detecting moving objects [11].…”
Section: Introductionmentioning
confidence: 99%